2014
DOI: 10.1093/pcp/pct202
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Highly Dynamic F-Actin Plus Ends in Growing Phaseolus vulgaris Root Hair Cells and Their Responses to Rhizobium etli Nod Factors

Abstract: Legume plants secrete signaling molecules called flavonoids into the rhizosphere. These molecules activate the transcription of rhizobial nod genes, which encode proteins involved in the synthesis of signaling compounds named Nod factors (NFs). NFs, in turn, trigger changes in plant gene expression, cortical cell dedifferentiation and mitosis, depolarization of the root hair cell membrane potential and rearrangement of the actin cytoskeleton. Actin polymerization plays an important role in apical growth in hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 55 publications
0
40
0
Order By: Relevance
“…Nowadays, microscopic approaches to study cytoskeleton dynamics and reorganization have been improved , and thus they may allow deeper insight into the host/ microbe interactions in space and time (Perrine-Walker et al, 2014;Zepeda et al, 2014). In the following sections, the host cytoskeletal responses upon symbiotic or pathogenic plant-microbe interactions will be examined.…”
Section: Role Of Plant Cytoskeleton In Plant Biotic Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, microscopic approaches to study cytoskeleton dynamics and reorganization have been improved , and thus they may allow deeper insight into the host/ microbe interactions in space and time (Perrine-Walker et al, 2014;Zepeda et al, 2014). In the following sections, the host cytoskeletal responses upon symbiotic or pathogenic plant-microbe interactions will be examined.…”
Section: Role Of Plant Cytoskeleton In Plant Biotic Interactionsmentioning
confidence: 99%
“…Mutations in NAP1 and PIR1 genes showed that these SCAR/WAVE complex proteins are essential for root hair, trichome and infection thread growth (Miyahara et al, 2010). Recently, a quantitative assessment of actin microfilament dynamics during apical growth was carried out using substoichiometric concentrations of fluorescently labeled cytochalasin D below its IC50 (concentration of cytochalasin D exhibiting half-maximal inhibitory activity against actin microfilament polymerization) which purportedly marks barbed ends of filamentous actin where actin nucleation occurs (Zepeda et al, 2014). After exposure to Nod factor, number of plus actin ends significantly increased in Phaseolus vulgaris root hairs and these plus ends relocalized to the site of infection thread.…”
Section: Cytoskeleton and Plant Symbiotic Interactions With Bacteriamentioning
confidence: 99%
“…9 In this work, we examined the distribution of polymerizing actin using confocal microscopy. Although the fluorescently tagged plus ends were mainly localized in the tip region, some actin foci were distributed in the cytoplasm.…”
Section: Actin Plus Ends Are Closely Associated With the Tip Domementioning
confidence: 99%
“…Furthermore, using a low concentration of fluorescently labeled cytochalasin, we recently reported that free actin plus ends (i.e., growing or polymerizing ends) are located in the tip region of growing root hairs. 9 Under such low, sublethal concentrations, the intensity of the actin polymerization signal in the tip increased in growing root hair cells treated with Rhizobium etli nodulation factors (NFs), declined during the swelling response, and was restored to normal levels when tip growth was reinitiated. This finding adds weight to the idea that actin polymerization plays a key role in the tip region of growing root hair cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation